Asbestos between science and myth. A 6,000-year story - Bianchi, Claudio; Bianchi, Tommaso (La Medicina del Lavoro, 2015)
Asbestos was used in making pottery in Eastern Finland from around 4000 B.C. In the ancient era and in the Middle Ages, magic properties were frequently attributed to this mineral. In the first century A.D., the Latin encyclopaedist Pliny the Elder reported in his Historia Naturalis that asbestos protects against all poisonings, particularly that of magicians. Moreover, asbestos was often found in places of worship, in Rome as well as in Athens and in Jerusalem. In the Middle Ages asbestos was identified with some animals, such as the salamander and certain white rodents. With such appearance, the mineral had a huge success in Western as well as in Eastern literature and the fine arts. Marco Polo (1254-1324) in the Milione tried to deny that asbestos was a salamander. Despite its noxious effects, asbestos continues to be used in much of the world. In the 21st century it seems to be maintaining its quality as a magic stone.